Growth and phytomass production of maize varieties in different fallow management - Borges, Anna Christina Monteiro Roffé; Kato, Osvaldo Ryohei; Pinheiro, Hugo Alves; Shimizu, Maurício Kadooka; Rangel-Vasconcelos, Lívia Gabrig Turbay; de Oliveira Júnior, Moisés Cordeiro Mourão (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the growth and phytomass production of three maize varieties under different fallow management in a slash and mulch system, in Marapanim, northeast of Pará state, Brazil, during the dry season. The experimental design was a randomized blocks, with 18 treatments and four replicates. The plots consisted of three fallow management: natural, enriched with inga (Inga edulis) and tachi-branco (Sclerolobium paniculatum), and enriched with inga and tachi-branco with phosphorus fertilization. Three maize varieties (BRS Sol da Manhã, BRS 4154 Saracura and BR 106) were introduced and distributed in split-plots with or without additional fertilization (NPK). The variables evaluated were plant height, stem diameter, leaf number, mass of moist and dry matter, and stand. The fallow management with enriched fallow and enriched fallow with phosphorus positively influenced plant height, stem diameter, and moist and dry mass production; the additional fertilization potentialized the effect of fallow management on these variables.